Vibration-damping adhesive composition
Patent Information
- Application Number
- CN202080106913.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-11-05
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2040-11-05
AI Technical Summary
然而,当前焙烘窗口要求高能量输入,不符合全球节约能源的趋势
[0016] The present invention also relates to the cured product of the aforementioned vibration-damping adhesive composition. The cured vibration-damping adhesive composition exhibits excellent shear strength on a variety of substrates and displays a good appearance.
Smart Images

Figure BDA0004208417070000071 
Figure BDA0004208417070000081 
Figure BDA0004208417070000082
Abstract
Description
Technical Field
[0001] This invention relates to an anti-flutter adhesive composition comprising: a) at least one olefinically unsaturated rubber; b) at least one PVC homopolymer with a K value of 67 to 75; c) at least one PVC copolymer with a K value of 60 to 75; d) at least one epoxy resin; e) at least one epoxy curing agent; f) at least one first organic peroxide with a decomposition temperature of 125 to 180°C; and g) at least one second organic peroxide with a decomposition temperature below 125°C. The anti-flutter adhesive composition can be cured over a wide temperature range and exhibits excellent shear strength and a good appearance after curing. Background Technology
[0002] Vibration damping adhesives are mostly used to bond the inner and outer panels of automotive components and to reduce any vibrations between the inner and outer panels relative to each other. Typically, depending on the automotive production line, the vibration damping adhesive is heated in a baking window of 170 to 200°C to allow it to cure properly. However, current baking windows require high energy input, which is inconsistent with global energy conservation trends.
[0003] Therefore, there is a need to develop a vibration damping adhesive that can cure at a lower temperature range of 150 to 170°C to save energy, and more preferably, it can cure over a wide temperature range of 150 to 200°C so that it can be applied to different automotive production lines. Summary of the Invention
[0004] This invention relates to a vibration damping adhesive composition comprising:
[0005] a) At least one type of olefinically unsaturated rubber;
[0006] b) At least one PVC homopolymer with a K value of 67 to 75;
[0007] c) At least one PVC copolymer with a K value of 60 to 75;
[0008] d) At least one epoxy resin;
[0009] e) At least one epoxy curing agent;
[0010] f) at least one first organic peroxide with a decomposition temperature of 125 to 180 °C; and
[0011] g) At least one second organic peroxide with a decomposition temperature below 125°C;
[0012] in
[0013] Based on the total weight of the composition, the amount of the first organic peroxide is 0.4 to 0.8% by weight; and
[0014] Based on the total weight of the composition, the amount of the second organic peroxide is 0.2 to 1% by weight.
[0015] The vibration damping adhesive composition can be cured at a temperature ranging from 150 to 200°C.
[0016] The present invention also relates to the cured product of the aforementioned vibration-damping adhesive composition. The cured vibration-damping adhesive composition exhibits excellent shear strength on a variety of substrates and displays a good appearance.
[0017] The present invention also relates to articles bonded by the cured product of the said vibration damping adhesive composition or articles filled with the cured product of the said vibration damping adhesive composition. Detailed Implementation
[0018] The invention is described in more detail in the following paragraphs. Each aspect thus described may be combined with any one or more other aspects unless explicitly indicated otherwise. In particular, any feature indicated as preferred or advantageous may be combined with any one or more other features indicated as preferred or advantageous.
[0019] In the context of this invention, the terminology used should be interpreted according to the following definitions, unless the context otherwise indicates.
[0020] As used herein, the singular forms “a” and “the” include both a singular and a plural referent, unless the context clearly indicates otherwise.
[0021] The terms “comprising,” “containing,” and “including” as used herein are synonymous with “containing” and are inclusive or open-ended and do not exclude additional unlisted members, elements, or method steps.
[0022] The enumeration of numerical endpoints includes all numbers and decimals falling into the corresponding range, as well as the listed endpoints.
[0023] All references cited in this specification are incorporated herein by way of citation.
[0024] Unless otherwise defined, all terms (including technical and scientific terms) used in this disclosure shall have the meanings commonly understood by one of ordinary skill in the art to which this invention pertains. Further guidance, including terminology definitions, is provided to better understand the teachings of this invention.
[0025] In the context of this disclosure, certain terms are used.
[0026] The term "olefinically unsaturated" refers to at least one non-aromatic unsaturated site.
[0027] The term "rubber" refers to a polymer that can return to its original shape after being stretched or deformed.
[0028] The term "K-value" is used to describe the degree of polymerization of a polymer. It is determined according to DIN EN ISO 1628-2.
[0029] The term "decomposition temperature" refers to the temperature at which 50% of the peroxide substantially dissociates / decomposes into free radicals capable of initiating other reactions within one hour. It is determined by pyrolysis gravimetric analysis (TGA). Preferably, a TA instrument Q500 is used for analysis under nitrogen at a heating rate of 5 °C / min.
[0030] Alkene-bonded unsaturated rubber
[0031] The vibration-damping adhesive composition of the present invention comprises at least one olefinically unsaturated rubber. Suitable olefinically unsaturated rubbers include natural rubber, synthetic rubber, and mixtures thereof. In some embodiments, the olefinically unsaturated rubber preferably has a number-average molecular weight of 30,000 g / mol or higher—e.g., 50,000 g / mol, 100,000 g / mol, and 300,000 g / mol—as measured by GPC.
[0032] Representative examples of suitable synthetic rubbers include, but are not limited to, styrene-butadiene rubber (SBR), styrene-butadiene-vinylpyridine rubber, chloroprene rubber, isoprene rubber (IR), isoprene-isobutylene rubber (IIR), polybutadiene rubber (BR), ethylene-propylene-diene monomer terpolymer (EPDM), acrylonitrile-butadiene rubber (NBR), polysiloxanes containing ethylenic unsaturation, polyurethanes containing ethylenic unsaturation, and mixtures thereof.
[0033] In some embodiments, the olefinically unsaturated rubber is preferably styrene-butadiene rubber (SBR), polybutadiene rubber (BR), or a mixture thereof.
[0034] Examples of commercially available olefinically unsaturated rubbers include: SBR1009 from Lion Elastomer; BR 9000 from Beijing Yanshan Petrochemical Rubber & Plastics Chemical Co., Ltd.; and BR 9000 from Sinopec Gaoqiao Petrochemical Co., Ltd.
[0035] In some embodiments of the invention, the amount of olefinically unsaturated rubber is 2 to 10% by weight, and preferably 4 to 8% by weight, based on the total weight of the damping adhesive composition.
[0036] PVC polymer
[0037] The vibration damping adhesive composition of the present invention comprises: at least one PVC homopolymer with a K value of 67 to 75, and at least one PVC copolymer with a K value of 60 to 75.
[0038] PVC copolymers can be obtained by copolymerizing vinyl chloride with one or more olefinically unsaturated comonomers. Comonomers that can be used in the formation of PVC copolymers include, but are not limited to: vinylidene halides, such as vinylidene chloride or vinylidene fluoride; vinyl carboxylates, such as vinyl acetate, vinyl propionate, or vinyl butyrate; vinyl aromatic derivatives, such as styrene or vinylnaphthalene; and olefins, such as ethylene, propylene, or 1-butene.
[0039] In some embodiments of the present invention, the PVC homopolymer preferably has a K value of 68 to 71.
[0040] In some embodiments of the invention, the PVC copolymer preferably has a K value of 63 to 70.
[0041] Surprisingly, when PVC homopolymers and PVC copolymers with suitable K values are incorporated into the composition, the vibration damping adhesive composition can be cured over a wide temperature range, and the cured product has a good appearance and excellent shear strength on a variety of substrates (e.g., aluminum plates, cold-rolled steel, and galvanized steel).
[0042] Examples of commercially available PVC homopolymers include VESTOLIT E7031 and P 1353K from VESTOLIT GmbH & Co. KG. Examples of commercially available PVC copolymers include PCMA12 from Shenyang Chemical Co., Ltd., and Lacovyl PA 1384 from Arkema.
[0043] In some embodiments of the invention, the amount of PVC homopolymer is preferably 6 to 15% by weight, more preferably 7 to 10% by weight, and even more preferably 8 to 9% by weight, based on the total weight of the vibration damping adhesive composition.
[0044] In some embodiments of the invention, the amount of PVC copolymer is preferably 2 to 5% by weight, and more preferably 3 to 4% by weight, based on the total weight of the vibration damping adhesive composition.
[0045] Epoxy resin
[0046] The vibration-damping adhesive composition of the present invention comprises at least one epoxy resin. The epoxy resin can be any common epoxy resin containing at least one epoxy group per molecule—and preferably multiple epoxy groups per molecule. Examples of epoxy resins include, but are not limited to, bisphenol A epoxy resin, bisphenol F epoxy resin, biphenyl epoxy resin, naphthalene epoxy resin, diphenyl ether epoxy resin, diphenyl sulfide epoxy resin, hydroquinone epoxy resin, biphenyl phenolic epoxy resin, cresol phenolic epoxy resin, phenolic epoxy resin, bisphenol A phenolic epoxy resin, trisphenol epoxy resin, tetraphenylolethane epoxy resin, and any combination thereof.
[0047] Examples of commercially available epoxy resins include: DER331 from Olin Corporation; EPON 828 from Shell Chemical Corporation; YD-128 from Kukdo Chemical Co., Ltd.; and EPICLON N-665 from Dainippon Ink and Chemicals Inc.
[0048] In some embodiments of the invention, the amount of epoxy resin is preferably 1 to 6% by weight, and more preferably 3 to 5% by weight, based on the total weight of the vibration damping adhesive composition.
[0049] Epoxy curing agent
[0050] The vibration-damping adhesive composition of the present invention comprises at least one epoxy curing agent. An epoxy curing agent refers to any curing agent commonly used in epoxy systems, including but not limited to polyamides, amines, imidazoles, and their derivatives. Exemplary curing agents include dicyandiamide, polyamide resins based on dimer fatty acids and polyamines, methyldiethanolamine, triethanolamine, diethylaminopropylamine, benzyldimethylamine, m-xylylenedi(dimethylamine), benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, 1-methylimidazole, 2-methylimidazole, and 2,4-diethylimidazole.
[0051] Examples of commercially available epoxy curing agents include: Versamid 140 from Gabriel Performance Products; Ancamine TEPA from Evonik; Ajicure PN-H from Ajinomoto Fine-Techno Co., Ltd.; Fujicure-FXR-1090FA from T&K Toka; 1,2-dimethylimidazole from Shikoku Chemicals Corporation; 2E4MI from Evonik; Gaskamine 240 from Mitsubishi Gas Chemical; and Ecure 14 from Alz Chem.
[0052] In some embodiments of the invention, the amount of epoxy curing agent is preferably 0.01 to 2% by weight, and more preferably 0.4 to 0.8% by weight, based on the total weight of the vibration damping adhesive composition.
[0053] Organic peroxides
[0054] The vibration damping adhesive composition of the present invention comprises: at least one first organic peroxide with a decomposition temperature of 125 to 180°C, and at least one second organic peroxide with a decomposition temperature of less than 125°C.
[0055] In some embodiments of the present invention, the first organic peroxide preferably has a decomposition temperature of 130 to 160°C, and more preferably 130 to 140°C.
[0056] In some embodiments of the present invention, the first organic peroxide is preferably dicumyl peroxide.
[0057] In some embodiments of the present invention, the second organic peroxide preferably has a decomposition temperature of 50 to 120°C, more preferably 80 to 120°C, and even more preferably 100 to 115°C.
[0058] In some embodiments of the present invention, the second organic peroxide is preferably 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane.
[0059] Examples of first organic peroxides include, but are not limited to, dicumyl peroxide (DCP), bis(tert-butyl) peroxide, and 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexyne (DBPH).
[0060] Examples of second organic peroxides include, but are not limited to, bis(2,4-dichlorobenzoyl)peroxide (DCBP), benzoyl peroxide, and 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane.
[0061] Examples of commercially available first organic peroxides include DCP from Taicang Plastic Additives Factory Co., Ltd., and DCP-40 from Jiangsu Daoming Chemical Co., Ltd.
[0062] Examples of commercially available second organic peroxides include Varox 231XL from Vanderbilt Chemicals, LLC; and TMCH-40 from United Initiators Inc.
[0063] In some embodiments of the invention, the amount of the first organic peroxide is 0.4 to 0.8% by weight, and preferably 0.5 to 0.7% by weight, based on the total weight of the damping adhesive composition.
[0064] In some embodiments of the invention, the amount of the second organic peroxide is 0.2 to 1% by weight, and preferably 0.3 to 0.4% by weight, based on the total weight of the damping adhesive composition.
[0065] Surprisingly, when two organic peroxides with suitable decomposition temperatures are incorporated into the composition, the vibration damping adhesive composition can be cured over a wide temperature range, and the cured product has a good appearance and excellent shear strength on a variety of substrates (e.g., aluminum sheet, cold-rolled steel, and galvanized steel).
[0066] Moreover, it was surprisingly found that PVC homopolymers and PVC copolymers with suitable K values, as well as two organic peroxides with suitable decomposition temperatures, can work synergistically to achieve curing of the vibration damping adhesive composition over a wide temperature range.
[0067] Optional additives
[0068] The vibration-damping adhesive composition may also contain optional additives. The selection of additives suitable for the vibration-damping adhesive compositions of the present invention depends on the specific intended use of the vibration-damping adhesive composition and can be determined by those skilled in the art in each case.
[0069] <Nano-inorganic fillers>
[0070] The vibration-damping adhesive composition of the present invention may optionally contain at least one nano-sized inorganic filler. The nano-sized inorganic filler of the present invention preferably has a 70% volume particle size (D70) of 20 to 80 nm, more preferably a D70 of 40 to 60 nm, and even more preferably a D70 of 50 to 55 nm. The D70 value refers to the point where 70% by volume of particles in the cumulative volume distribution curve have a diameter smaller than said value. The particle size of the nano-sized inorganic filler is determined by laser diffraction, preferably using a Partica LA-950 laser scattering particle size analyzer available from Horiba.
[0071] An example of a commercially available nano-inorganic filler is TA 17 from Wuhu Zhuoyue Nanomaterials Co., Ltd.
[0072] In some embodiments of the invention, the amount of nano-inorganic filler is preferably 0 to 30% by weight, more preferably 10 to 30% by weight, and even more preferably 15 to 20% by weight, based on the total weight of the vibration damping adhesive composition.
[0073] <Pyrolytic Silica>
[0074] The vibration damping adhesive composition of the present invention may optionally contain at least one BET surface area of 150 to 250 m². 2 / g, preferably 170 to 230m 2 / g of pyrolytic silica. The BET surface area value is determined according to GB / T 10722.
[0075] An example of commercially available pyrolytic silica is CAB-O-SIL M-5 from Cobot Corporation.
[0076] In some embodiments of the invention, the BET surface area is 150 to 250 m² based on the total weight of the vibration-damping adhesive composition. 2 The amount of pyrolytic silica is preferably 0 to 3% by weight, more preferably 1.5 to 3% by weight, and even more preferably 2 to 3% by weight.
[0077] Surprisingly, it was found that the anti-sagging properties of the vibration-damping adhesive composition were significantly improved when nano-inorganic particles with suitable BET surface areas and pyrolytic silica were incorporated into the composition. This is important for vibration-damping adhesive compositions, which are typically applied to automotive panels with large gaps. If the adhesive composition sags, the cured product will have degraded appearance and vibration-damping properties.
[0078] <Plasticizer>
[0079] The vibration-damping adhesive composition of the present invention may optionally contain at least one plasticizer. The plasticizer of the present invention refers to any common plasticizer known in the art. Examples of plasticizers include, but are not limited to: epoxy resin-based plasticizers (e.g., epoxidized soybean oil, epoxidized linseed oil, and epoxidized cottonseed oil), phosphate esters, aliphatic esters, aromatic esters, dioctyl terephthalate (DOTP), dioctyl phthalate (DOP), di(isononyl) phthalate (DINP), di(isodecyl) phthalate (DIDP), diundecyl phthalate (DUP), dioctyl adipate (DOA), diisononyl adipate (DINA), trioctyl trimellitate (TOTM), trioctyl phosphate (TOP), tricresyl phosphate (TCP), etc. Plasticizers may be used alone or in any combination.
[0080] Examples of commercially available plasticizers include: DOTP from China National Pharmaceutical Group; DOA from Wengiang Chemical; and DINP from Taizhou Liancheng Chemical Co., Ltd.
[0081] In some embodiments of the invention, the amount of plasticizer is 0 to 40% by weight, and preferably 15 to 30% by weight, based on the total weight of the damping adhesive composition.
[0082] <Heat stabilizer>
[0083] The vibration-damping adhesive composition of the present invention may optionally contain at least one heat stabilizer. The heat stabilizer of the present invention refers to any common heat stabilizer known in the art that functions to protect the PVC polymer during the heating process. Examples of heat stabilizers include, but are not limited to, methyltin thiols, butyltin thiols, and octyltin thiols.
[0084] In some embodiments of the invention, the amount of heat stabilizer is 0 to 0.2% by weight, and preferably 0.01 to 0.1% by weight, based on the total weight of the damping adhesive composition.
[0085] <Foaming Agent>
[0086] The vibration-damping adhesive composition of the present invention may optionally contain at least one foaming agent known in the art. The foaming agent induces gas formation, which then creates chambers to form a porous structure in the cured product of the vibration-damping adhesive composition. The foaming agent of the present invention may be a physical foaming agent, a chemical foaming agent, or a combination of both. Examples of foaming agents include, but are not limited to, carbon dioxide gas, nitrogen, air, halogenated hydrocarbons, bicarbonates, azo compounds, and hydrazine derivatives.
[0087] In some embodiments of the invention, the amount of foaming agent is 0 to 1% by weight, and preferably 0.2 to 0.6% by weight, based on the total weight of the damping adhesive composition.
[0088] Crosslinking agent
[0089] The vibration-damping adhesive composition of the present invention may optionally contain at least one crosslinking agent known in the art. The crosslinking agent preferably has at least two olefinically unsaturated groups. Examples of crosslinking agents include, but are not limited to: diacrylates, such as zinc dimethacrylate and magnesium dimethacrylate; acrylates and methacrylates of alcohols, such as trimethylolpropane trimethacrylate; and vinyl acrylates.
[0090] In some embodiments of the invention, the amount of crosslinking agent is 0 to 10% by weight, and preferably 0.1 to 5% by weight, based on the total weight of the vibration damping adhesive composition.
[0091] <Thermoexpandable microspheres>
[0092] The damping adhesive composition of the present invention may optionally contain at least one thermally expandable microsphere known in the art for aiding in the foaming of the composition. The thermally expandable microspheres may be formed by enclosing a substance that readily becomes gaseous and expands upon heating (e.g., isobutane, propane, pentane, methylbutane) within an elastic shell. The elastic shell may be made of a substance that melts or bursts due to thermal expansion. Examples of such substances constituting the shell include, but are not limited to, vinylidene chloride / acrylonitrile copolymer, acrylonitrile / methacrylonitrile copolymer, poly(methyl methacrylate), polyacrylonitrile, poly(vinylidene chloride), etc.
[0093] Examples of commercially available thermally expandable microspheres include, for example, Matsumoto Microsphere from Matsumoto Yushi-Seiyaku Co., Ltd., and Advancell EM H204 from Seikisui Chemical Co., Ltd.
[0094] In some embodiments of the invention, the amount of thermally expandable microspheres is 0 to 1% by weight, and preferably 0.2 to 0.4% by weight, based on the total weight of the damping adhesive composition.
[0095] <Other Inorganic Packing Materials>
[0096] The vibration damping adhesive composition of the present invention may optionally contain at least one additional inorganic filler different from the nano-inorganic filler, said additional inorganic filler preferably having a 70% volume particle size (D70) greater than 500 nm. Examples of the additional inorganic filler include, but are not limited to: calcium carbonate; and metal oxides, such as titanium dioxide, magnesium oxide, zinc oxide, iron oxide, chromium oxide, zirconium oxide, and aluminum oxide.
[0097] In some embodiments of the invention, the amount of additional inorganic filler is 0 to 10% by weight, and preferably 2 to 6% by weight, based on the total weight of the damping adhesive composition.
[0098] Other optional additives that may be used in the damping adhesive composition of the present invention include, but are not limited to: antioxidants; antimicrobial agents; dyes; pigments and mixtures thereof.
[0099] In a preferred embodiment, the vibration damping adhesive composition comprises:
[0100] 2 to 10% by weight of at least one olefinically unsaturated rubber;
[0101] 6 to 15% by weight of at least one PVC homopolymer with a K value of 67 to 75;
[0102] 2 to 5% by weight of at least one PVC copolymer with a K value of 60 to 75;
[0103] 1 to 6% by weight of at least one epoxy resin;
[0104] At least one epoxy curing agent, ranging from 0.01 to 2% by weight;
[0105] 0.4 to 0.8% by weight of at least one first organic peroxide with a decomposition temperature of 125 to 180 °C;
[0106] 0.2 to 1% by weight of at least one second organic peroxide with a decomposition temperature below 125°C;
[0107] At least one nano-inorganic filler, ranging from 0 to 30% by weight;
[0108] At least one BET with a surface area of 150 to 250 m² is present in an amount of 0 to 3% by weight. 2 / g of pyrolytic silica;
[0109] At least one plasticizer, ranging from 0 to 40% by weight;
[0110] At least one heat stabilizer, ranging from 0 to 0.2% by weight;
[0111] At least one foaming agent, ranging from 0 to 1% by weight;
[0112] At least one crosslinking agent, ranging from 0 to 10% by weight;
[0113] 0 to 10% by weight of at least one other inorganic filler; and
[0114] At least one thermally expandable microsphere, ranging from 0 to 1% by weight;
[0115] The total weight percentage of all components is 100% by weight.
[0116] The vibration-damping adhesive composition of the present invention can be prepared by uniformly mixing the following substances: at least one olefinically unsaturated rubber, at least one PVC homopolymer with a K value of 67 to 75, at least one PVC copolymer with a K value of 60 to 75, at least one epoxy resin, at least one epoxy curing agent, at least one first organic peroxide with a decomposition temperature of 125 to 180°C, at least one second organic peroxide with a decomposition temperature below 125°C, together with optionally present additives; wherein the additives are, for example, at least one nano-inorganic filler, at least one BET surface area of 150 to 250 m². 2 / g of pyrolytic silica, at least one plasticizer, at least one heat stabilizer, at least one foaming agent, at least one crosslinking agent, at least one additional inorganic filler, and at least one thermally expandable microsphere.
[0117] The vibration damping adhesive composition of the present invention can be applied to the surface of a substrate by means of a scraper, sprayer or extruder and cured at a temperature in the range of 150 to 200°C.
[0118] The shear strength of the vibration damping adhesive composition of the present invention on various substrates (including cold-rolled steel, galvanized steel and aluminum plate) after curing at different temperatures can be measured according to SAE J1523 by bonding two substrates together with the adhesive composition.
[0119] The vibration damping adhesive composition of the present invention preferably has a shear strength greater than or equal to 0.2 MPa after curing at a temperature in the range of 150 to 200°C, and the cured adhesive completely separates from the surface of one substrate after the two substrates are pulled apart.
[0120] The appearance of the cured damping adhesive composition of the present invention can be evaluated by examining the tackiness of the surface of the cured damping adhesive composition and whether it is elastic and whether there are cracks on the surface by pressing with a finger.
[0121] The cured damping adhesive composition of the present invention is preferably elastic, non-sticky, and free of cracks on the surface.
[0122] The anti-sagging properties of the adhesive composition of the present invention after curing at different temperatures can be evaluated according to GB / T 31113-2014.
[0123] The cured damping adhesive composition preferably has dislocations of less than or equal to 5 mm.
[0124] Example:
[0125] The present invention will be further described in detail and illustrated with reference to the following embodiments. These embodiments are intended to help those skilled in the art better understand and practice the invention, but are not intended to limit the scope of the invention. All figures in the embodiments are based on weights unless otherwise stated.
[0126] Example 1-22
[0127] The following materials are used in the embodiments.
[0128] BR 9000 (butadiene rubber from Beijing Yanshan Petrochemical Rubber & Plastics Chemical Co., Ltd.);
[0129] SBR 1009 (styrene-butadiene rubber from Lion Elastomer);
[0130] PCMA 12 (a vinyl chloride / vinyl acetate copolymer with a K value of 63.3 to 67.6 from Shenyang Chemical Co., Ltd.);
[0131] Vestolit E 7031 (a homopolymer of polyvinyl chloride with a K value of 68 to 71 from Vestolit GmbH & Co. KG);
[0132] PB 1702 (a homopolymer of polyvinyl chloride with a K value of 79 from Anhui Tianchen Chemical Co., Ltd.);
[0133] FORMOLON PR-450 (a homopolymer of polyvinyl chloride with a K value of 65 from Formosa Plastics Corporation);
[0134] Lacovyl PA 1384 (a vinyl chloride / vinyl acetate copolymer with a K value of 69 from Arkema);
[0135] YD-128 (an epoxy resin derived from bisphenol A from Kukdo Chemical Co., Ltd.);
[0136] Ecure 14 (dicyandiamide from Alz Chem);
[0137] Varox 231 XL (1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane from Vanderbilt Chemicals LLC, with a decomposition temperature of 115 °C);
[0138] DCP (dicumyl peroxide with a decomposition temperature of 135℃ from Taicang Plastic Additives Factory Co., Ltd.);
[0139] TMCH-40 (bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane from United Initiators Inc., with a decomposition temperature of 114°C);
[0140] Luvomaxx K CDO 65W (from Lehmann & Voss & Co., 1,4-benzoquinone dioxime with a decomposition temperature of 223°C);
[0141] TA 17 (nano-calcium carbonate with a particle size (D70) of 50nm from Wuhu Zhuoyue Nanomaterials Co., Ltd.);
[0142] CAB-O-SIL M-5 (from Cabot Corporation, with a surface area of 175 to 225 m²) 2 / g of pyrolytic silica);
[0143] ESO (epoxidized soybean oil from Tongxiang Chemical Co., Ltd.);
[0144] DINP (di(isononyl) phthalate from Taizhou Liancheng Chemical Co., Ltd);
[0145] 56060K (octyltin thiolate from Galate Chemicals);
[0146] AC 7000 (azodicarboamide from Shanghai Hanjin Chemical Co., Ltd.);
[0147] Dymalink 708 (zinc dimethacrylate from Cray Valley);
[0148] SR 350 (trimethylolpropane trimethacrylate from Sartomer);
[0149] CaO (calcium oxide from Shanghai Fanhua Inorganic Chemical Co., Ltd.);
[0150] ZnO (zinc oxide from US Zinc (Changshu) Metal Co., Ltd.);
[0151] N-CaCO3 (calcium carbonate from Shanghai Bazishi Powder Factory); and
[0152] Advancell EM H 204 (methylbutane encapsulated in acrylonitrile methyl acrylonitrile copolymer from Sekisui Chemical Co., Ltd.).
[0153] The vibration damping adhesive composition was prepared as an example using the components according to Tables 1a and 1b. The components were mixed under vacuum using a kneader (LK11 1 from Hermann Linden Maschinenfabrik) at 30 rpm for 100 minutes. During preparation, the temperature was controlled at approximately 35°C and the vacuum level was controlled at approximately 0.7 MPa.
[0154] The vibration damping adhesive composition was then subjected to various tests, and the results are reported in Tables 2 to 6.
[0155] Table 1a. Vibration damping adhesive compositions
[0156]
[0157]
[0158] Table 1b. Vibration damping adhesive compositions
[0159]
[0160]
[0161] Test methods
[0162] <Shear strength>
[0163] The shear strength of the damping adhesive composition was determined according to SAE J1523. A substrate was provided and prepared by wiping it with acetone and allowing it to air dry for 5 minutes. The damping adhesive composition was extruded onto the surface of the substrate, and two substrates were mated together to form a 25x25 mm overlap adhesive area and a 3 mm adhesive thickness. The damping adhesive composition was cured for 40 minutes at the desired temperature of 150 to 200°C using a BINDER M115 oven. The shear strength value was measured using a Zwick Z010 at a drag rate of 50 mm / min.
[0164] The result is acceptable if the shear strength value is greater than or equal to 0.2 MPa and the cured adhesive completely separates from the surface of a substrate (100% CF).
[0165] The result is unacceptable if the shear strength value is greater than or equal to 0.2 MPa, but the cured adhesive breaks and remains on the surfaces of both substrates after the two substrates are pulled apart (e.g., 80% of the cured adhesive remains on one substrate and 20% of the cured adhesive remains on the other substrate (80% CF)).
[0166] <Appearance>
[0167] Provide cold-rolled steel with dimensions of 100*50*0.8mm (length*width*thickness). Extrude the damping adhesive composition onto the surface of the cold-rolled steel to form an adhesive strip with dimensions of 80*10*6mm (length*width*thickness). Place the cold-rolled steel in a BINDER M115 oven and cure the adhesive strip at a desired temperature of 150 to 200°C for 40 minutes. Allow the cured adhesive strip to cool at room temperature for 24 hours.
[0168] The appearance of the cured adhesive strip is inspected by pressing its surface with a finger. If the cured adhesive strip is elastic, non-sticky, and free of cracks, the result is reported as "OK". If the cured adhesive has any of the above defects, the result is reported as "Fail".
[0169] <Anti-sagging feature>
[0170] The anti-sagging properties of the vibration damping adhesive composition were determined according to GB / T 31113-2014. Cold-rolled steel with dimensions of 100*50*0.8mm (length*width*thickness) was provided. The vibration damping adhesive composition was extruded onto the surface of the cold-rolled steel to form an upright cylinder (cylinder) with a diameter of 22mm and a height of 15mm. The cold-rolled steel was then tilted at a 70-degree angle, and the cylindrical vibration damping adhesive composition was left on the cold-rolled steel at 25°C for 30 minutes. The dislocations of the vibration damping adhesive composition were recorded.
[0171] The inclined cold-rolled steel and the damping adhesive composition on the surface of the steel were further cured in a BINDER M115 oven at 155°C for 30 minutes. Dislocations of the damping adhesive composition were also recorded.
[0172] If the dislocations of the cylindrical damping adhesive composition are less than or equal to 5 mm at both 25°C and 155°C, the anti-sagging properties of the damping adhesive composition are acceptable.
[0173] Table 2a Shear strength of cold-rolled steel
[0174]
[0175] Table 2b. Shear strength of cold-rolled steel
[0176]
[0177]
[0178] Table 3a. Shear strength on galvanized steel
[0179]
[0180] Table 3b. Shear strength on galvanized steel
[0181]
[0182]
[0183] Table 4a. Shear strength on aluminum plates
[0184]
[0185] Table 4b. Shear strength (MPa) on aluminum plates
[0186]
[0187] Table 5a. Appearance of cured damping adhesive compositions
[0188]
[0189] Table 5b. Appearance of cured damping adhesive compositions
[0190]
[0191] The shear strength of the vibration damping adhesive compositions to various substrates after curing is reported in Tables 2 to 4, and the appearance of the cured vibration damping adhesive compositions is reported in Table 5. It was found that the following are necessary for the vibration damping adhesive compositions: the inclusion of at least one PVC homopolymer with a K value of 67 to 75, at least one PVC copolymer with a K value of 60 to 75, at least one first organic peroxide with a decomposition temperature of 125 to 180°C, and at least one second organic peroxide with a decomposition temperature below 125°C, thereby ensuring that the shear strength of the vibration damping adhesive composition after curing is greater than or equal to 0.2 MPa. Furthermore, the cured vibration damping adhesive composition completely separates from one substrate after being pulled apart, and the cured vibration damping adhesive composition has a good appearance. When the K value of the PVC copolymer, the decomposition temperature of the organic peroxide, the amount of PVC polymer, or the amount of organic peroxide is not within the desired range, the shear strength of the vibration damping adhesive composition after curing or the appearance of the cured vibration damping adhesive composition deteriorates, as shown in Examples 5 to 8 and Examples 13 to 17.
[0192] Table 6a. Anti-sagging properties of vibration damping adhesive compositions
[0193]
[0194] Table 6b. Anti-sagging properties of vibration damping adhesive compositions
[0195]
[0196] The anti-sagging properties of the vibration-damping adhesive compositions are reported in Table 6. It was found that the following are necessary for the vibration-damping adhesive compositions: the inclusion of at least one nano-inorganic filler and at least one BET surface area of 150 to 250 m². 2 / g of pyrolytic silica, thereby giving the vibration damping adhesive composition excellent anti-sagging properties. If either the nano-inorganic filler or the pyrolytic silica is missing from the composition, or if the amount of the nano-inorganic filler or the pyrolytic silica is not within the desired range, the cured vibration damping adhesive composition has large dislocations, as demonstrated in Examples 21 and 22.
Claims
1. A vibration-damping adhesive composition comprising: a) At least one type of olefinically unsaturated rubber; b) At least one PVC homopolymer with a K value of 67 to 75; c) At least one PVC copolymer with a K value of 60 to 75; d) At least one epoxy resin; e) At least one epoxy curing agent; f) at least one first organic peroxide with a decomposition temperature of 125 to 180 °C; and g) At least one second organic peroxide with a decomposition temperature below 125°C; in Based on the total weight of the composition, the amount of the first organic peroxide is 0.4 to 0.8% by weight. Based on the total weight of the composition, the amount of the second organic peroxide is 0.2 to 1% by weight; and The K value is used to describe the degree of polymerization of the polymer and is determined according to DIN EN ISO 1628-2.
2. The vibration damping adhesive composition according to claim 1, wherein the PVC homopolymer has a K value of 68 to 71.
3. The vibration damping adhesive composition according to claim 1 or 2, wherein the amount of the PVC homopolymer is 6 to 15% by weight based on the total weight of the composition.
4. The vibration damping adhesive composition according to claim 3, wherein the amount of the PVC homopolymer is 7 to 10 by weight based on the total weight of the composition.
5. The vibration damping adhesive composition according to claim 4, wherein the amount of the PVC homopolymer is 8 to 9 by weight based on the total weight of the composition.
6. The vibration damping adhesive composition according to claim 1 or 2, wherein the PVC copolymer has a K value of 63 to 70.
7. The vibration damping adhesive composition according to claim 1 or 2, wherein the amount of the PVC copolymer is 2 to 5% by weight based on the total weight of the composition.
8. The vibration damping adhesive composition according to claim 7, wherein the amount of the PVC copolymer is 3 to 4 by weight based on the total weight of the composition.
9. The vibration damping adhesive composition according to claim 1 or 2, wherein the first organic peroxide has a decomposition temperature of 130 to 160°C.
10. The vibration damping adhesive composition according to claim 9, wherein the first organic peroxide has a decomposition temperature of 130 to 140°C.
11. The vibration damping adhesive composition according to claim 1 or 2, wherein the first organic peroxide is dicumyl peroxide.
12. The vibration damping adhesive composition according to claim 1 or 2, wherein the amount of the first organic peroxide is 0.5 to 0.7 by weight based on the total weight of the composition.
13. The vibration damping adhesive composition according to claim 1 or 2, wherein the second organic peroxide has a decomposition temperature of 50 to 120°C.
14. The vibration damping adhesive composition according to claim 13, wherein the second organic peroxide has a decomposition temperature of 80 to 120°C.
15. The vibration damping adhesive composition according to claim 14, wherein the second organic peroxide has a decomposition temperature of 100 to 115°C.
16. The vibration damping adhesive composition according to claim 1 or 2, wherein the second organic peroxide is 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane.
17. The vibration damping adhesive composition according to claim 1 or 2, wherein the amount of the second organic peroxide is 0.3 to 0.4 by weight based on the total weight of the composition.
18. The vibration-damping adhesive composition according to claim 1 or 2, further comprising at least one nano-inorganic filler and at least one BET surface area of 150 to 250 m². 2 / g of pyrolytic silica.
19. The vibration damping adhesive composition of claim 18, wherein the amount of the nano-inorganic filler is 10 to 30% based on the total weight of the composition.
20. The vibration damping adhesive composition of claim 19, wherein the amount of the nano-inorganic filler is 15 to 20% based on the total weight of the composition.
21. The vibration damping adhesive composition of claim 18, wherein the amount of pyrolytic silica is 1.5 to 3% based on the total weight of the composition.
22. The vibration damping adhesive composition of claim 21, wherein the amount of pyrolytic silica is 2 to 3% based on the total weight of the composition.
23. The vibration-damping adhesive composition according to claim 1, comprising: (a) 2 to 10% by weight of at least one olefinically unsaturated rubber; (b) 6 to 15% by weight of at least one PVC homopolymer with a K value of 67 to 75; (c) 2 to 5% by weight of at least one PVC copolymer with a K value of 60 to 75; (d) 1 to 6% by weight of at least one epoxy resin; (e) 0.01 to 2% by weight of at least one epoxy curing agent; (f) 0.4 to 0.8% by weight of at least one first organic peroxide with a decomposition temperature of 125 to 180 °C; (g) 0.2 to 1% by weight of at least one second organic peroxide with a decomposition temperature below 125°C; (h) 0 to 30% by weight of at least one nano-inorganic filler; (i) 0 to 3% by weight of at least one BET with a surface area of 150 to 250 m² 2 / g of pyrolytic silica; (j) 0 to 40% by weight of at least one plasticizer; (k) 0 to 0.2% by weight of at least one heat stabilizer; (l) at least one foaming agent, ranging from 0 to 1% by weight; (m) 0 to 10% by weight of at least one crosslinking agent; (n) 0 to 10% by weight of at least one other inorganic filler different from the nano-inorganic filler; and (o) 0 to 1% by weight of at least one thermally expandable microsphere; The total weight percentage of all components is 100%.
24. The cured product of the vibration damping adhesive composition according to any one of claims 1 to 23.
25. Articles bonded to or filled with the cured product according to claim 24.
Citation Information
Patent Citations
Mold release agent and preparation method and application thereof
CN101875220A
Vibration-damping reinforcing composition, vibration-damping reinforcing member, and vibration-damping reinforcing method for thin plate
CN101889051A